Current Progress of Jatropha Curcas Commoditisation as Biodiesel Feedstock: A Comprehensive Review - Riayatsyah, T. M. I.; Sebayang, A. H.; Silitonga, A. S.; Padli, Y.; Fattah, I. M. R.; Kusumo, F.; Ong, H. C.; Mahlia, T. M. I. (Frontiers in Energy Research, 2022)
This article looks at the national and global actors, social networks, and narratives that have influenced Jatropha’s worldwide acceptability as a biofuel crop. Jatropha Curcas is a genus of around 175 succulent shrubs and trees in the Euphorbiaceae family (some of which are deciduous, such as Jatropha Curcas L.). It’s a drought-tolerant perennial that thrives in poor or marginal soil and produces a large amount of oil per hectare. It is easy to grow, has a fast growth rate, and can generate seeds for up to 50 years. Jatropha Curcas has been developed as a unique and promising tropical plant for augmenting renewable energy sources due to its various benefits. It is deserving of being recognised as the only competitor in terms of concrete and intangible environmental advantages. Jatropha Curcas is a low-cost biodiesel feedstock with good fuel properties and more oil than other species. It is a non-edible oilseed feedstock. Thus it will have no impact on food prices or the food vs fuel debate. Jatropha Curcas emits fewer pollutants than diesel and may be used in diesel engines with equivalent performance. Jatropha Curcas also makes a substantial contribution to the betterment of rural life. The plant may also provide up to 40% oil yield per seed based on weight. This study looks at the features characteristics of Jatropha Curcas as biodiesel feedstock and performance, and emissions of internal combustion engine that operates on this biodiesel fuel.